Pelatihan penulisan artikel ilmiah penelitian tindakan kelas untuk publikasi pada jurnal iIlmiah - Patrisius Afrisno Udil (Jurnal Nasional Pengabdian Masyarakat, 2021)
One of the classical issues teachers face in East Nusa Tenggara is the lack of academic articles based on scientific research, including Classroom Action Research (CAR). It was happened because of the low interest, motivation, and ability of teachers to write the research in the form of an academic article and publish it in an academic journal. Therefore, it was essential to hold training on writing CAR articles for publication in academic journals. It aims to improve the ability of teachers to write CAR article and publish it in academic journals. This activity is running in the form of online training. The methods used in implementing activities include webinars through zoom meetings, presentations, discussion, training, and mentoring through WhatsApp Group. This activity hold in two stages, namely the preparation stage and the implementation stage. The result of the activity indicates the high enthusiasm of participants both during the webinar and training and mentoring. In addition, this activity can also improve the participants' understanding and abilities in making or writing good CAR article for publication in academic journals